Spiral springs for timekeeping movements

A ternary alloy composition for spiral springs, incorporating elements like Ta and V to optimize thermoelastic coefficient and mechanical properties, addresses production challenges and enhances performance and efficiency in portable watch springs.

JP7610685B2Active Publication Date: 2025-01-08NIVAROX FAR SA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023192852
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-16
Filing Date
2023-11-13
Publication Date
2025-01-08
Estimated Expiration
2042-03-15

AI Technical Summary

Technical Problem

Existing spiral springs for portable watches face challenges such as high elastic limit, difficult production, poor fatigue resistance, and thermoelastic coefficient (TC) deviations, leading to long production times and material brittleness, especially in Nb-Ti binary alloys.

Method used

A ternary alloy composition using Nb, Ti, and additional elements like Ta, V, Zr, Hf, W, and Mo, with controlled proportions to optimize TC and reduce secondary errors, enhancing mechanical properties and production efficiency.

Benefits of technology

The new alloy composition achieves improved elastic limit, reduced secondary errors, and accelerated production times, resulting in high-performance spiral springs suitable for portable watches with stable chronometric performance across varying temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610685000001
    Figure 0007610685000001
  • Figure 0007610685000002
    Figure 0007610685000002
  • Figure 0007610685000003
    Figure 0007610685000003
Patent Text Reader

Abstract

To develop chemical composition of a spiral spring without fragile phases and with reduced production time and reduced secondary error.SOLUTION: A spiral spring intended to be equipped with a balance of a horological movement is made of an alloy consisting of: Nb and Ti elements, at least one element selected from V and Ta, optionally at least one element selected from Zr and Hf, optionally at least one element selected from W and Mo, optionally traces of other elements selected from O, H, C, Fe, N, Ni, Si, Cu and Al. In the alloy, the total content of Nb, V and Ta is 40-85 wt.%, the total content of Ti, Zr and Hf is 15-55 wt.%, the W content and the Mo content are each 0-2.5 wt.%, and the content of each of the elements selected from O, H, C, Fe, N, Ni, Si, Cu and Al is 0-1600 ppm with the total content of the trace elements being 0.3 wt.% or less. The invention further relates to a production method thereof.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a spiral cam intended to equip the balance of a timepiece movement. The present invention further relates to a method for manufacturing this spiral spring. [Background technology]

[0002] In the manufacture of spiral springs for portable timepieces (e.g. wristwatches, pocket watches), - High elastic limit - Easy to produce, especially by drawing and rolling - Excellent fatigue resistance - Stable performance over time - Small cross section We are faced with seemingly irreconcilable constraints.

[0003] In addition, the alloy selected for the spiral spring must be designed to be suitable for assembling such a spiral spring. The watch is designed to maintain its chronometric performance even when used at a wide range of temperatures. Therefore, the thermoelastic coefficient (TEC) of the alloy is very important. To create a chronometric oscillator with a balance of CuBe or German silver, , the thermoelastic coefficient must be within the range of ±10 ppm / ℃.

[0004] Thermoelastic coefficient of alloy, expansion coefficient of spiral spring (α) and expansion coefficient of balance (β) The equation relating

[0005]

number

[0006] where the variable M is the rate in s / d, the variable T is the temperature in °C, and E is the is the Young's modulus of the spiral alloy, and (1 / E)(dE / dT) is the thermoelastic coefficient of the spiral alloy. and the expansion coefficient is °C. -1 It is represented as:

[0007] In practice, TC is calculated as follows:

[0008]

number

[0009] This value must be within the range of -0.6 to +0.6 s / d°C.

[0010] Spiral springs for the manufacture of portable watches typically contain Ti between 40 and 60% by weight. %, especially known from prior art binary Nb-Ti alloys such as 47 wt.% Nb. By applying the deformation and heat treatment diagram, this spiral spring contains Nb in the β phase and Nb in the α phase. It has a two-phase microstructure with Ti in the form of precipitates. The cold-worked β-phase Nb has a strong positive The thermoelastic coefficient of Ti in the α phase is strongly negative, which allows the two-phase alloy The thermoelastic coefficient of gold can approach zero, which is particularly favorable for TC.

[0011] However, there are some challenges when using binary Nb-Ti alloys in spiral springs. The binary alloy of Nb-Ti is particularly preferred when TC is low as mentioned above. The composition is a rate that is approximated above by a straight line passing through two points (8°C and 38°C). It is not optimized for quadratic error, which is a measure of curvature. This rate is 8° and 38°. There can be deviations from this linear behavior between °C, and the quadratic error at 23 °C is , is a measure of this deviation at a temperature of 23 °C. Typically, for NbTi47 alloy, The secondary error should be 4.5s / d, preferably within the range of -3 to +3s / d. be.

[0012] Another challenge with binary Nb-Ti alloys is the loss of adhesion after the winding step, mainly during the settling step. This step is important because the precipitation of Ti occurs in the spiral. This allows the shape of the spring to be established and a TC close to zero after Ti precipitation. In fact, the precipitation time is very long, ranging from 8 to 30 hours for the NbTi47 alloy. On average, it takes about 20 hours. This makes production times very long. Apart from the problem of long production times, too much Ti can lead to brittle martensite. A phase may form, which makes it difficult to deform the material to produce the spiral spring. Thus, it is recommended not to add too much Ti to the alloy. .

[0013] Even today, TC is still kept low for the production of spiral springs. It is designed to meet various requirements such as no weak phase, short production time, and small secondary errors. New chemical compositions such as these need to be developed. Summary of the Invention [Problem to be solved by the invention]

[0014] The present invention provides a new chemical composition of a spiral spring that can solve the above problems. The purpose of this study is to propose the following. [Means for solving the problem]

[0015] For this purpose, the present invention provides a method for manufacturing a steel sheet made of at least a ternary alloy based on Nb and Ti. According to the present invention, Nb is the secondary error. It is preferably partially replaced by Ta and / or V to reduce the In addition, Ti is partially replaced by Zr and / or Hf, thereby maintaining the same TC. While maintaining the above-mentioned condition, the deposition is accelerated during the settling process, i.e., the driving force of deposition is increased. The presence of at least three elements in a large proportion of the alloy improves the alloy's mechanical properties, In particular, the elastic limit can be improved.

[0016] In particular, the invention is intended to equip the balance of a timepiece movement. The spiral spring is Nb and Ti elements, and at least one element selected from V and Ta; If present, at least one element selected from Zr and Hf; If present, at least one element selected from W and Mo; and If present, other elements selected from O, H, C, Fe, N, Ni, Si, Cu and Al. and trace elements and wherein the alloy is made of at least a ternary alloy consisting of: The total content of Nb, V and Ta is 40 to 85% by weight, The total content of Ti, Zr and Hf is 15 to 55% by weight, The contents of W and Mo are 0 to 2.5 wt.%, respectively. The content of each element selected from O, H, C, Fe, N, Ni, Si, Cu and Al is The total amount of the trace elements is 0.3% by weight or less.

[0017] Preferably, the Nb content is greater than 45 wt. %, which provides a strong positive thermoelastic This strongly positive thermoelastic coefficient is due to the presence of Ti, Zr, and Hf. This is intended to be compensated for by the negative thermoelastic coefficient of the α phase.

[0018] Preferably, the Ti content is 15% by weight or more.

[0019] The invention further relates to a method for manufacturing a spiral spring for such a watch.

[0020] Other features and advantages of the present invention can be realized by reading the following detailed description. do. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention relates to at least a ternary alloy comprising Nb, Ti, and one or more additional elements. This invention relates to a spiral spring for a watch made by

[0022] According to the invention, the alloy comprises: the elements Nb and Ti, and at least one element selected from V and Ta; - if present, at least one element selected from Zr and Hf; - if present, at least one element selected from W and Mo, and - if present, other elements selected from O, H, C, Fe, N, Ni, Si, Cu and Al and trace elements, The total content of Nb, V and Ta is 40 to 85% by weight, and preferably the content of Nb is greater than 45% by weight, or even 50% by weight or more; The total content of Ti, Zr and Hf is 15 to 55% by weight, and the content of Ti is preferably The amount is 15% by weight or more, - The W and Mo contents are 0-2.5 wt.% each; - The content of each element selected from O, H, C, Fe, N, Ni, Si, Cu and Al is The total amount of the trace elements is 0.3% by weight or less.

[0023] According to the invention, Nb is partially replaced by Ta and / or V. The partial replacement of Nb by a and / or V is intended to reduce secondary errors. The binary Nb- Tests were performed on V and Nb-Ta alloys. Secondary errors were measured at 23°C. This is the linear relationship between the rate at 8°C and the rate at 38°C versus the rate at 23°C. For example, the rates at 8°C, 23°C, and 38°C are chi) Can be measured using a chronoscope type device.

[0024] Table 1 below shows the pure Nb-V and Nb-Ta alloys as a function of their weight percentages of V and Ta. The reference data and values ​​for pure Nb, pure V, pure Ta and NbTi47 alloy are shown. Pure Nb has a secondary error of -6.6s / d at 23°C. Adding Ti The precipitation of Ti in the α phase in NbTi47 alloy by This significantly increases the value of the pure V and pure Ta, compensating for the negative effect of Nb. Nb, and have secondary errors that are more negative than -24.9 and -28.7 s / The partial replacement of Nb by V and / or Ta reduces the secondary error by -7 Therefore, it is possible to reduce the V or Ta to a negative value smaller than s / d. Increasing the Nb substitution rate by 5% to 25% reduces the secondary error from about -7s / d to - Thus, to reach values ​​in this range, V or Ta, Or Nb can be replaced by a combination of V and Ta. The secondary error is T The content when the content of a alone, V alone, or the total content of Ta and V is 5% by weight to 25% by weight. In the case of the secondary error, the secondary error is within the range of -7s / d to -12s / d. Ta alone, V alone, Ta and V combined content is 10% by weight to 25% by weight, preferably 15% by weight When the content is less than 25% by weight, it is within the range of -9s / d to -12s / d. During the fixing step, one or more elements that form the α-phase precipitates in the Nb-V / Ta alloy are added. By adding Preferably, the total content of all elements forming the α phase of the precipitate is 15% by weight to 5. 5% by weight. The element forming the α-phase is at least Ti, preferably 15% by weight. That is all. In addition to Ti, it can be Hf and / or Zr, which is defined as During the deposition step, a single α-layer of precipitates is formed with Ti. When the alloy contains Zr and Hf, the total content of Zr and Hf is 1 to 40% by weight, preferably 5 to 25% by weight. %, more preferably 10 to 25% by weight, and further preferably 15 to 25% by weight.

[0025] [Table 1]

[0026] The alloy further includes 0 to 2.5 weight percent of the alloy to increase the Young's modulus of the alloy. The spring may contain W and Mo in a content of 100% by weight, so that the spring can be rotated at a given torque. The thickness of the spiral spring can be reduced to make the spiral spring lighter.

[0027] In a particularly preferred form, the alloys used in the present invention are free of potential unavoidable trace elements. It does not contain any other elements except for inorganic matter.

[0028] Specifically, the oxygen content is 0.10% by weight or less, and even 0.085% by weight or less. % by weight or less.

[0029] Specifically, the carbon content is 0.04% by weight or less of the total, and particularly 0.020% by weight or less of the total. % or less, and even 0.0175% by weight or less of the total.

[0030] Specifically, the iron content is 0.03% by weight or less, particularly 0.025% by weight or less. Further, the content is 0.020% by weight or less of the total.

[0031] Specifically, the nitrogen content is 0.02% by weight or less, particularly 0.015% by weight or less. % or less, and even 0.0075% by weight or less of the total.

[0032] Specifically, the hydrogen content is 0.01% by weight or less of the total, and particularly 0.0035% by weight or less of the total. % or less, and even 0.0005% by weight or less of the total.

[0033] Specifically, the silicon content is 0.01% by weight or less of the total.

[0034] Specifically, the nickel content is 0.01% by weight or less, and especially 0.16% by weight or less. The amount is less than %.

[0035] Specifically, the copper content is 0.01% by weight or less, particularly 0.005% by weight or less. The following is the result.

[0036] Specifically, the aluminum content is 0.01% by weight or less of the total.

[0037] Preferably, the spiral spring comprises a single β phase of Nb, V and / or Ta, and If the alloy contains Hf and / or Zr, it may contain Ti and a single alpha phase of Hf and / or Zr. In the presence of Ta and V, this microstructure is further expanded to include TaV2. To achieve such a microstructure, the microstructure may include any of the intermediate metallic materials described below. In order to achieve this, it is necessary to precipitate the α phase (Ti, Hf, Zr) by heat treatment.

[0038] The balance spring made of this alloy has a strength of 500 MPa or more, especially 500 to 1000 MPa. Preferably, the balance spring has an elastic limit of 100 GPa or more. , and preferably has an elastic modulus of 110 GPa or more.

[0039] The invention further relates to a method for manufacturing a balance spring for a watch, said method comprising the steps of: teeth, a) preparing or providing a blank made of the alloy; b) the Ti, and Zr and / or Hf, if present, of said alloy are substantially in the form of a solid solution; and the blank is subjected to a β-type quench so that Nb, Ta and / or V are in the β phase. and c) subjecting the alloy to a deformation sequence followed by a heat treatment; and d) winding to form a spiral spring, followed by a final heat treatment. The alloy is the elements Nb and Ti, and at least one element selected from V and Ta; - if present, at least one element selected from Zr and Hf; - if present, at least one element selected from W and Mo, and - if present, other elements selected from O, H, C, Fe, N, Ni, Si, Cu and Al and trace elements, The total content of Nb, V and Ta is 40 to 85% by weight, and the content of Nb is preferably The amount is greater than 45% by weight, The total content of Ti, Zr and Hf is 15 to 55% by weight, and the content of Ti is preferably The content is 15% by weight or more (including the boundary), - The W and Mo contents are 0-2.5 wt.% each; - Content of each element selected from O, H, C, Fe, N, Ni, Si, Cu and Al is 0 to 1600 ppm, and the total of the trace elements is 0.3 wt % or less. Deformation means deformation by stretching and / or rolling. In stretching, if necessary , one or more dies need to be used in the same sequence or in different sequences. Drawing is carried out until a round cross-section wire is obtained. Rolling has the same deformation cycle as drawing. Preferably, the alloy is The final sequence is rolling, preferably at the entrance section of the winding pin. Use a rectangular profile that matches the profile of the

[0040] In these combined deformation-heat treatment sequences, each deformation is assigned a given number ranging from 1 to 5. This deformation satisfies the traditional equation 2ln(d0 / d), where d0 is the diameter of the final beta quench and d is the diameter of the cold-worked wire. The global accumulation of deformations over the entire sequence results in a total deformation between 1 and 14 Each combined deformation-heat treatment sequence produces α phase (Ti, Zr and / This includes performing a heat treatment to precipitate Hf.

[0041] The beta quench prior to the deformation and heat treatment sequence is carried out at temperatures between 700°C and 1000°C under vacuum. It is a dissolution treatment carried out at room temperature for a duration of 5 minutes to 2 hours, followed by cooling under gas. The beta quench is a melting process that lasts for one hour at 800°C in a vacuum. Afterwards it is cooled under gas.

[0042] To return to the combined deformation-heat treatment sequence, the heat treatment is carried out at temperatures between 300°C and 700°C. It is a precipitation treatment carried out at 400℃ to 600℃ for 1 to 200 hours. At the holding temperature, the duration is 5 hours to 30 hours.

[0043] In particular, the method involves a number of combined deformation-heat treatment sequences ranging from 1 to 5.

[0044] In particular, the first combined deformation-heat treatment sequence reduces the cross section by at least 30%. The first transformation process is performed as follows:

[0045] In particular, each of the combined deformation-heat treatment sequences that is not the first deformation treatment , a process of deformation between the two heat treatments is carried out, which reduces the cross section by at least 25%.

[0046] In particular, after the alloy blank is made and before the deformation-heat treatment sequence, additional In the next step, copper, nickel, cupronickel, cupronmanganese, gold, silver, A table of ductile materials selected from nickel phosphorus (Ni-P) and nickel boron (Ni-B) A surface layer is added to the blank to facilitate forming it into a wire shape during deformation. After the heat treatment sequence or after the winding step, the wire may be damaged, especially by chemical attack. A layer of ductile material is removed from the wire.

[0047] Instead, the surface layer of ductile material is spun into a spit whose pitch is not a multiple of the blade thickness. In another variant, a surface layer of ductile material is deposited on the surface of the conductor. The layers are deposited in such a way that they form a spring with a fluctuating pitch.

[0048] Therefore, in a particular timepiece application, the ductile material or copper may be used at a given time. This makes it easy to form the wire into a thickness of 10 to 500 μm. The wire is then cut so that the wire remains on the wire and has a final diameter of 0.3-1 mm. By mechanical attack, a layer of ductile material or copper is removed, rolled flat, and then wired. The actual spring is manufactured by printing.

[0049] The preparation of the ductile material or copper may be done galvanically or mechanically. In this case, a ductile material or copper jacket or tube is fitted over a larger diameter alloy rod, The composite rod is then thinned in a deformation process.

[0050] The removal of the layer can be achieved in particular by chemical attack using a solution based on cyanide or an acid, such as nitric acid. This can be done by attacking.

[0051] The final heat treatment is carried out at a temperature between 300°C and 700°C for a duration between 1 hour and 200 hours. In particular, the duration is 5 to 30 hours at a holding temperature of 400 to 600°C. During the final heat treatment, the precipitation of the α phase is completed. The heat treatment time can be reduced by several hours, typically at a holding temperature of 400°C to 600°C. The session lasts for 4 to 8 hours.

[0052] By appropriately combining deformation and heat treatment sequences, it is possible to obtain nanometer-scale structures , Nb, Ta and / or V in the beta phase, and Ti, and Zr and / or Hf (Zr in the alloy) and Hf (when either or both are present), The alloy has a very high strength of at least 500 MPa. It has an elastic limit and an elastic modulus of more than 100 GPa. This combination of properties is The alloy according to the invention is also very suitable for use in lubricating springs, as well as for ductile materials or copper. It can be easily covered, which greatly promotes deformation by stretching. do.

[0053] Also, Nb, Ti, Ta and / or other metals of the type mentioned above selected to implement the invention. At least ternary type alloys containing V are suitable for use in the normal operating temperature range of wristwatches. It has an effect similar to that of "Elinvar", whose thermoelastic coefficient is essentially zero. Suitable for manufacturing self-compensating spiral springs.

Claims

1. A spiral spring intended to equip the balance of a timepiece movement, said spiral spring comprising: Nb and Ti elements, and at least one element selected from V and Ta; At least one element selected from Zr and Hf; Optionally, at least one element selected from W and Mo; and Other trace elements selected from O, H, C, Fe, N, Ni, Si, Cu and Al; and wherein the alloy is made of an alloy consisting of The total content of Nb, V and Ta is 40 to 85% by weight, The total content of Ti, Zr and Hf is 15 to 55 wt. %; The contents of W and Mo are each 0 to 2.5 wt.%; The content of each element selected from O, H, C, Fe, N, Ni, Si, Cu, and Al is 0 to 1600 ppm, and the total content of the trace elements is 0.3 wt% or less; The content of Zr or Hf, or the total content of Zr and Hf, is 5 to 25% by weight, and the total content of V and Ta is 5 to 25% by weight. Spiral spring characterized by:

2. The Nb content is greater than 45 wt.%.

2. The spiral spring according to claim 1 .

3. The total content of V and Ta is 10 to 25 wt%.

3. The spiral spring according to claim 1 or 2.

4. The total content of V and Ta is 15 to 25 wt%.

4. The spiral spring according to claim 1, wherein the spiral spring is a spiral spring having a diameter of 100 mm or more.

5. Contains Zr and / or Hf, and the total content of Zr and Hf is 10 to 25 wt %.

5. The spiral spring according to claim 1, wherein the spiral spring is a spiral spring having a diameter of 100 mm or more.

6. Contains Zr and / or Hf, and the total content of Zr and Hf is 15 to 25 wt %.

6. The spiral spring according to claim 1, wherein the spiral spring is a spiral spring having a diameter of 100 mm or more.

7. Having a microstructure containing β phases of Nb, V and / or Ta, and α phases of Ti, and, if the alloy contains Zr and / or Hf, Zr and / or Hf.

7. The spiral spring according to claim 1, wherein the spiral spring is a spiral spring having a diameter of 100 mm or more.

8. The elastic limit is 500 MPa or more and the elastic modulus is 100 GPa or more.

8. The spiral spring according to claim 1, wherein the spiral spring is a spiral spring having a diameter of 100 mm or more.

9. The elastic modulus is 110 GPa or more.

9. The spiral spring according to claim 8.

10. A method for manufacturing a spiral spring according to any one of claims 1 to 9 intended to equip the balance of a timepiece movement, comprising the steps of: forming a blank from at least a ternary alloy; subjecting the blank to a beta-quench such that the Ti of the alloy is substantially in solid solution, the Nb, and V and / or Ta are in the beta phase, and if the alloy contains Zr and / or Hf, the Zr and / or Hf of the alloy are also substantially in solid solution; subjecting the alloy to a sequence of deformations followed by intermediate heat treatments; a winding step for winding to form a spiral spring; and performing a final heat treatment; and the alloy is Nb and Ti elements, and at least one element selected from V and Ta; Optionally, at least one element selected from Zr and Hf; Optionally, at least one element selected from W and Mo; and and other trace elements selected from O, H, C, Fe, N, Ni, Si, Cu, and Al; In the alloy, The total content of Nb, V and Ta is 40 to 85% by weight, The total content of Ti, Zr and Hf is 15 to 55 wt. %; The contents of W and Mo are each 0 to 2.5 wt.%; The content of each element selected from O, H, C, Fe, N, Ni, Si, Cu, and Al is 0 to 1600 ppm, and the total content of the trace elements is 0.3 wt% or less; The content of Zr or Hf, or the total content of Zr and Hf, is 5 to 25% by weight, and the total content of V and Ta is 5 to 25% by weight. A method comprising:

11. The beta-quench is a melting treatment carried out under vacuum at a temperature of 700°C to 1000°C for a duration of 5 minutes to 2 hours, followed by cooling under gas.

11. The method of claim 10.

12. The final and intermediate heat treatments of each sequence are precipitation treatments of α-phase Ti, and, if the alloy contains Zr and / or Hf, Zr and / or Hf, at holding temperatures between 300°C and 700°C for durations between 1 hour and 200 hours.

12. The method according to claim 10 or 11.

13. When the alloy contains Zr and / or Hf, the final heat treatment is performed at a holding temperature of 400°C to 600°C for a duration of 4 to 8 hours.

13. The method according to any one of claims 10 to 12.

14. After the step of preparing the blank and before the steps of performing the deformation sequence and thereafter performing an intermediate heat treatment, a surface layer of a ductile material selected from copper, nickel, cupro-nickel, cupro-manganese, gold, silver, nickel-phosphorus (Ni-P) and nickel-boron (Ni-B) is added to the blank to facilitate forming into a wire, and before or after the winding step, the layer of ductile material is removed from the wire by chemical attack. The method according to any one of claims 10 to 13.

Citation Information

Patent Citations

  • Method for manufacturing a spiral spring for a watch movement.

    CH716155A2

  • Hyomenochokokashita kyojingokin

    JP1976072913A

  • Self-compensated hair spring and its production

    JP1999071625A

  • Spring, spiral spring and hair spring for watch, and watch

    JP2005140674A

  • Method for manufacturing balance spring for horological movement

    JP2020183940A